2020
DOI: 10.1108/ijif-09-2018-0097
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual framework of internal Sharīʿah audit effectiveness factors in Islamic banks

Abstract: Purpose Sharīʿah audit is an important area to examine because it is considered the backbone of the Islamic finance industry. The purpose of this study is to spot and highlight the determinants that have an effect on internal Sharīʿah audit effectiveness in the Islamic banking industry. It attempts to develop a conceptual framework for those factors. Design/methodology/approach The paper reviews the existing literature to figure out the factors that frame the effectiveness of internal Sharīʿah audit in Islam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…First, it examines the organisational commitment and its effect on turnover intention amongst employees of IBs during the 2020 lockdown period in various Arab countries. This lockdown arguably created enormous confusion that was translated by the switch of many employees across IBs during the lockdown, perhaps because the lockdown was generally viewed as a direct cause of the economic crisis (Algabry et al, 2020). Indeed, the lockdown that hit major Arab countries in 2020 affected deeply the countries and the banks under investigation (Ali, 2020).…”
Section: Turnover Intentions For Ib Employeesmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it examines the organisational commitment and its effect on turnover intention amongst employees of IBs during the 2020 lockdown period in various Arab countries. This lockdown arguably created enormous confusion that was translated by the switch of many employees across IBs during the lockdown, perhaps because the lockdown was generally viewed as a direct cause of the economic crisis (Algabry et al, 2020). Indeed, the lockdown that hit major Arab countries in 2020 affected deeply the countries and the banks under investigation (Ali, 2020).…”
Section: Turnover Intentions For Ib Employeesmentioning
confidence: 99%
“…Several Islamic scholars (e.g. Algabry et al, 2020;Islam and Ahmad, 2020) argue that IBs are not only able to fight the economic effects of the pandemic and lockdown, but also have the capacity to come out as a substitute for the current financial system. Indeed, owing to their intrinsic power vis-a-vis the current financial system, IBs have a lot to offer.…”
Section: Turnover Intentions For Ib Employeesmentioning
confidence: 99%
“…The effective SA can be defined as the degree to which SA function achieved its established objectives to ensure an effective internal control system for Shariah compliance as outlined by the Shariah Governance Framework established by Bank Negara Malaysia. As shown in Figure 3, the study revealed many factors that could improve the performance and effectiveness of Shariah auditing in Islamic institutions, including competency (knowledge, skill and training), independence, Shariah auditor qualification, internal audit characteristics, external audit, audit committee attributes, Shariah supervisory board, top management and work performance (Ahmed and Sarea, 2019; Algabry et al , 2020; Ali and Kasim, 2019; Khalid, 2019; Khalid et al , 2017; Khalid, Haron, and Masron, 2018a; Khalid and Sarea, 2021; Mohd Ali et al , 2018). Effective SA function could provide reasonable assurance that Islamic financial activities and operations are Shariah-compliant.…”
Section: Thematical Analysismentioning
confidence: 99%
“…The role and responsibilities of auditors in IFIs are much broader than those found in conventional banks in relation to an examination of a variety of contracts, product structures, transactions reporting, preparation of financial statements, reports, marketing circulars and any other legal documents, which are pertinent to IFIs’ operations. Shariah auditors can take part in these responsibilities; they do not reject all the techniques and mechanisms of conventional auditing as they can be used to test the values that are in line with the Shariah (Algabry et al , 2020).…”
Section: Thematical Analysismentioning
confidence: 99%
“…Name internal factors and sharia internal audit structure, processes, and requirements [17]. Research conducted by Fadhistri and Dedik found that sharia compliance with proxy Islamic income ratio partially had no effect in the indication of fraud in Islamic banks.…”
Section: Nomentioning
confidence: 99%